Study of the influence of lubrication parameters on gear lubrication properties and efficiency. Issue 6 (12th September 2016) - Li, Kaiyue; Chen, Guoding; Liu, Deng
Abstract : Purpose: The analysis of lubricating properties and efficiency is important for aviation high-speed gear. So far, the project of lubricating properties and efficiency are processing under the condition of a given lubricating state, which is still depending on practical experience. This paper aims to mostly focus on the analysis of given lubricating state but lost sight of the relevance of lubrication parameters and lubricating state, which not only makes the analysis of aviation high-speed gear transmission and efficiency fail to trace to practical situation but also has an adverse effect on the reliance and validity of the project. Design/methodology/approach: Based on this, the numerical model of spraying oil and oil film spreading is established, and the quantitative relationship between spray lubrication parameters and spreading characteristics of oil film is studied. According to the geometric and mechanical conditions of meshing points and taking the influence of rich-oil/starved-oil lubrication and roughness of teeth surface into consideration, corrected film thickness under condition of elasto-hydrodynamic lubrication and lubricating state of mesh points are analyzed. On this basis, power consumption and efficiency of gear transmission are also calculated by figuring out the solid friction and oil friction separately. Findings: Through the research of this thesis, the effect of friction power consumption and efficiency with lubrication parameters is discussed. The effect of lubrication parameters on friction power consumption and efficiency of gear is complex. With the increase of spreading film thickness and film length, the frictional power consumption is less and the efficiency is higher. Originality/value: This work provides a systematic technological approach to lubrication design and efficiency calculation of aviation high-speed gear transmission, which has remarkable engineering significance for the accurate lubrication design of the aviation mechanical parts.